Otimização no planejamento agregado de produção em indústrias de processamento de suco concentrado congelado de laranja - Munhoz, José Renato (Universidade Federal de São Carlos, 2009)
This work aim at developing models using linear programming, goal programming and robust optimization to support decision making in the frozen concentrated orange juice planning process. The proposed model includes orange harvesting plan, which takes into account oranges maturation curves. This fact leads to a model that incorporates a large portion of the supply chain involved in the frozen concentrated orange juice sector. Another point to highlight is the inclusion of the blending process of different types of juices to match ratio specification of the product. This study uses orange acidity to calculate ratio specification of the product. This study also explores the importance of data uncertainty incorporation to the aggregate production planning for this business and evaluate results from different approaches of robust optimization to this problem. This author is not aware of previous work in the literature with such approach to the orange juice industry. The problem modeling uses blending problem concepts and production planning with multiple products, stages and periods concepts as well. To solve the linear programming, goal programming and robust optimization models, an algebraic modeling language and a state of art optimization solver of mathematical programming problems is used. A case study was developed in an orange juice company located in the São Paulo State. This company has many facilities and a worldwide distribution system, similar to other companies in this sector. The results show that the proposed approach can be used in real situations.
Keywords: Pesquisa operacional; Programação linear; Otimização; Suco de laranja - indústria; Planejamento de produção; Programação por metas; Estágios e períodos; Problemas de planejamento de produção com múltiplos produtos; Linear programming; Goal programming; Robust optimization; Blending process; Frozen concentrated orange juice; Production planning with multiple products; Stages and periods; ENGENHARIAS::ENGENHARIA DE PRODUCAO